Modelagem e simulação de sistema de controle de temperatura de chapa aquecedora - Segantini, Felipe Rinaldi de Oliveira (Universidade Federal de São Carlos, 2022)
With the advancements in information technology, the increase in global competition, in the demand for quality and also the hardening of ambiental laws, process control is becoming increasingly important to the formation of Chemical Engineers. These facts have produced an increasing demand for more efficiency in industrial processes, be them chemical processes, biochemical or other applicable, requiring more precise and reliable models to represent them and therefore, guarantee their operation in optimal conditions. For this purpose, there were made experiments using an Arduino-built system to collect temperature data in the ment the process would reach steady-state in a predetermined power range, allowing to obtain the convective coefficients used in this work to build the mathematical model. Analyzing the obtained convective coefficients, it is able to conclude that due to simplifications, the modelling of the heat transfer process didn't represent the process in an appropriate way, since the collected data produced lower values than expected by the literature. Afterwards, a simulation of the open loop system was made using the convective coefficients simulated in similar to the experiment's conditions and the results were close to the expected, showing a gradual variation in temperature until the system reached steady-state. By validating the open loop model, P, PI and PID controllers were implemented in a feedback configuration, by applying the Ziegler-Nichols and Tyreus-Luyben methods to parameter tuning. Observing their response curves, it is safe to affirm that the P and PI controller's responses were very few different than the expected for a dead-time system according to the literature, having also small dampening, but reaching values close to the setpoint. The PID controllers, although, didn't reach process stability, which indicates the control model needs more limitations to turn its controlling action closer to the actual. Furthermore, it is concluded that the modelling and simulation made in this study still needs refinements, given its potential as a didactic tool in the academical environment.
Modeling and simulation of a hot plate temperature control system
Keywords: Simulação; Controle; Transferência de calor; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA